Asymmetric axonal edge guidance: a new paradigm for building oriented neuronal networks. Issue 12 (26th May 2016) - Renault, Renaud; Durand, Jean-Baptiste; Viovy, Jean-Louis; Villard, Catherine
Abstract : We present a novel kind of directional axon guides for brain-on-a-chip applications. The axonal directional selectivity is created by rerouting axons growing in the unwanted direction back to their original compartment while leaving the other growth direction unaffected. Abstract : We present a novel kind of directional axon guides for brain-on-a-chip applications. Contrarily to previous works, the directionality in our design is created by rerouting axons growing in the unwanted direction back to their original compartment while leaving the other growth direction unaffected. This design yields state-of-the-art levels of directionality without the disadvantages of previously reported technologies.